Peer learning model in speech-language pathology student practicals in South Africa: A pilot study - K Coutts; N Barber (South African Medical Association, 2023)
Background. Given the current challenges of decreased clinical resources and the impact of COVID-19 restrictions on clinical training at sites, a shift inteaching models for practical placements for speech-language pathology (SLP) students in South Africa (SA) was required. The peer learning model thathas been trialled in the physiotherapy and nursing professions was piloted for this cohort of students to combat these restrictions.Objectives. To determine whether the peer learning model is an optimal supervision framework for final-year SLP students in the SA context for theadult neurology practical.Methods. This was a qualitative study that used a cohort of final-year SLP students. Once ethical clearance was obtained, data collection commencedusing various instruments, including self-reflection tools, questionnaires and pre- and post-interviews. Data were analysed using a top-down approachwhereby themes were generated and then further analysed.Results. Four themes emerged: power dynamics, theoretical skills, clinical skills and professionalism. Power dynamics was a novel finding of this studyand showed how a shift in power dynamics can facilitate the development of clinical skills. Peer learning appeared to improve clinical integration andclinical skills, including clinical writing and self-reflection.Conclusions. The piloting of the peer learning model appeared to be a success for final-year SLP students in an outpatient adult neurology setting. Thefindings from this study can assist in furthering studies in this context